ANALISIS KESELAMATAN DAN KESEHATAN KERJA DENGAN MENGGUNAKAN METODE HIRARC: SEBUAH STUDI KASUS - Adi, Prayonne (Universitas Majalengka, 2023)
This case study is situated in a manufacturing company operating in the production of PVC pipes in East Java, where human involvement plays a significant role in the production process. Through observations, numerous production and operational processes were found to pose risks to the safety and health of the workers. The abundance of potential hazards and risks to the safety and health of the workers needs to be reduced by implementing the HIRARC method. This method consists of a series of activities that begin with hazard identification, risk assessment, and the determination of control measures based on collected data. The analysis using the HIRARC method revealed the identification of 24 hazards, with 9 of them categorized as medium risk, and there were 11 types of activities/hazard risks classified as high risk, along with 4 extreme risk situations.